Do uncertainties and risks have an impact on cryptocurrency returns? Evidence from the symmetric and asymmetric Fourier quantile causality test; Las incertidumbres y los riesgos tienen impacto en los retornos de la criptomoneda? Evidencia de la prueba de causalidad cuántica simétrica y asimétrica de Fourier - Esra N. Kilci; Veli Yilanci (Estudios de Economía, 2025)
This paper explores the impact of uncertainties and risks on the returns of cryptocurrencies by considering the two dimensions of uncertainty sourcing from economic policy uncertainty and geopolitical risk. Therefore, we analyze whether there is a causality from the global economic policy uncertainty (GEPU) and geopolitical risk (GPR) to the cryptocurrency returns in the period from 2015:01 through 2023:05. In our analysis, we use the GEPU and GPR indexes as independent variables and the historical values of Bitcoin, Ethereum, Litecoin, Ripple, Monero, and Dash as dependent variables. We employ the Fourier augmented causality test considering the original series, and also the positive and negative components of the series. Our findings reveal that the GPR has predictive power for all cryptocurrencies while GEPU has not predictive power for only Bitcoin. Furthermore, we find evidence of the causality nexus that runs from negative shocks of GEPU to the negative shocks of Litecoin and Ripple, and from the negative shocks of GPR to the negative shocks of Litecoin and Monero indicating when there are significant decreases at the GEPU, these values can be used to predict the decreases of Litecoin and Ripple. Similarly, we can also imply it for the causality relationship from GPR to Litecoin and Monero. When we consider there might be a causal relationship not only between shocks of the same type but also between different types of shocks we find that there is unidirectional causality from negative shocks of GEPU to the positive shocks of Dash, Ethereum, and Monero at the high return phase, and from positive shocks of GEPU to the negative shocks of Ethereum, and from positive shocks of GPR to the negative components of Bitcoin, Ethereum, and Ripple at the bearish market conditions.
Keywords: C22; G15; D81; 330; Uncertainty; cryptocurrencies; geopolitical risk